2022
DOI: 10.1093/nar/gkac069
|View full text |Cite
|
Sign up to set email alerts
|

Transcription-replication coordination revealed in single live cells

Abstract: The coexistence of DNA replication and transcription during S-phase requires their tight coordination to prevent harmful conflicts. While extensive research revealed important mechanisms for minimizing these conflicts and their consequences, little is known regarding how the replication and transcription machinery are coordinated in real-time. Here, we developed a live-cell imaging approach for the real-time monitoring of replisome progression and transcription dynamics during a transcription-replication encou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…By monitoring fluorescent dot intensities in real time and measuring the time difference between the fluorescence increase midpoints of the two foci, a replication rate of single replisomes through the arrays can be calculated ( Figure 1 E). 27 , 30 , 31 , 32 Using this approach, we found that tetR-3HA labeled with 2E2-NLS-Envy allows monitoring tetO array duplication ( Figure 1 E). Measuring fork progression in these cells revealed similar replication times as the respective tetR-Envy strain ( Figure 1 F), demonstrating that 2E2-NLS-Envy tetR-3HA labeling can be used for the enhanced imaging of chromosomal loci in live yeast cells, as well as for monitoring replisome progression.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…By monitoring fluorescent dot intensities in real time and measuring the time difference between the fluorescence increase midpoints of the two foci, a replication rate of single replisomes through the arrays can be calculated ( Figure 1 E). 27 , 30 , 31 , 32 Using this approach, we found that tetR-3HA labeled with 2E2-NLS-Envy allows monitoring tetO array duplication ( Figure 1 E). Measuring fork progression in these cells revealed similar replication times as the respective tetR-Envy strain ( Figure 1 F), demonstrating that 2E2-NLS-Envy tetR-3HA labeling can be used for the enhanced imaging of chromosomal loci in live yeast cells, as well as for monitoring replisome progression.…”
Section: Resultsmentioning
confidence: 97%
“… 65 In addition, several studies have utilized scFvs for the detailed monitoring of protein translation while simultaneously labeling the translated RNA transcript in live cells. 21 , 61 , 62 , 63 , 64 Our development of the scFv approach in yeast, combined with the facile labeling of individual mRNAs, 32 , 66 highlight the potential for further development of the scFv approach for monitoring protein translation in live yeast cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[27] In addition, there are reports of transcription being locally inhibited during replication. [124,125] However, these examples of replication-transcription coordination do not appear to be timing specific. It is unclear how regulation of replication timing could fur-ther mitigate replication-transcription conflicts, because every gene gets replicated, regardless of when during S phase it happens.…”
Section: Why: Biological Significancementioning
confidence: 99%